2011
DOI: 10.1371/journal.pone.0026121
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Platform Array Screening Identifies COL1A2, THBS1, TNFRSF10D and UCHL1 as Genes Frequently Silenced by Methylation in Melanoma

Abstract: Epigenetic regulation of tumor suppressor genes (TSGs) has been shown to play a central role in melanomagenesis. By integrating gene expression and methylation array analysis we identified novel candidate genes frequently methylated in melanoma. We validated the methylation status of the most promising genes using highly sensitive Sequenom Epityper assays in a large panel of melanoma cell lines and resected melanomas, and compared the findings with those from cultured melanocytes. We found transcript levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 56 publications
2
64
0
Order By: Relevance
“…However, the expression levels of COL1A1 and COL1A2 in malignant tumors remain controversial. On one hand, frequent promoter methylation of COL1A1 was detected in renal cell carcinoma and hepatocellular carcinoma [9, 10], and COL1A2 was downregulated in melanoma [11], head and neck cancer [14], and bladder cancer [15]. On the other hand, COL1A1 and COL1A2 mRNA was upregulated in colorectal cancer and medulloblastoma [16, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expression levels of COL1A1 and COL1A2 in malignant tumors remain controversial. On one hand, frequent promoter methylation of COL1A1 was detected in renal cell carcinoma and hepatocellular carcinoma [9, 10], and COL1A2 was downregulated in melanoma [11], head and neck cancer [14], and bladder cancer [15]. On the other hand, COL1A1 and COL1A2 mRNA was upregulated in colorectal cancer and medulloblastoma [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, type I collagen is composed of two chains of collagen type I alpha 1 (COL1A1) and one chain of collagen type I alpha 2 (COL1A2) [5]. Recently, similar to the expressions of other members of the collagen family which is believed to be involved in carcinogenesis [68], abnormal expression of COL1A1 and COL1A2 has been reported in several cancers [911]. In addition, Zang et al [12] indentified that COL1A1 and COL1A2 were differentially expressed in gastric cancer by complementary DNA (cDNA) microarray.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma hypermethylation prevalence for ERα (50%), MGMT (50%), RARB2 (44%), RIL (88%), RASSF1A (69%), PAX7 (31%), PGRB (56%), PAX2 (38%), NKX2-3 (63%), OLIG2 (63%), HAND1 (63%), ECAD (88%), CDH13 (44%), MLH1 (0%), and p16 (6%) was reported [40]. Similarly, Bonazzi et al reported methylation of COL1A2 (24%), THBS1 (31%), TNFRSD10D (66%), and UCHL1 (42%) genes in 12 melanoma cell lines, relative to a reference pool of melanocytes [42]. More recent studies have integrated DNA methylation changes with transcriptional changes (RNA-Seq) and histone modifications (ChIP-Seq).…”
Section: Aberrant Methylation Changes In Melanomamentioning
confidence: 99%
“…[16][17][18][19] In addition, aberrant promoter methylation of these genes in melanoma tissues, cultured melanocytes or serum from melanoma patients has also been described. 17,18,[20][21][22][23][24][25][26][27] Total genomic DNA extraction Deterioration of DNA methylation levels in cultured PBMC samples has previously been reported. 28 To avoid this problem, we extracted total genomic DNA directly from cryopreserved primary PBMC cells (3-5 × 10 6 cells) using TRIzol ® as per manufacturers' guidelines.…”
Section: Gene Selectionmentioning
confidence: 99%